Flypaper Effect Analysis of General Allocation Fund and Local Own-Source Revenue on Expenditures in Kuningan Regency 2006 – 2020 - Agus Arifin; Nida Putri Awalia; Muhammad Farid Alfarisy; Joseph Yakatambu Yaramai (EKO-REGIONAL, 2023)
This research aims to analyze whether there is a flypaper effect of General Allocation Fund (GAF) and Local Own-Source Revenue (LOSR) on direct and indirect expenditures in Kuningan Regency in 2006 – 2020. Our research uses multiple linear regression, and we find that: (1) GAF and LOSR have positive and significant effect on both direct spending and indirect spending of regional government of Kuningan and (2) GAF has dominant effect on direct and indirect expenditures variables. We conclude that there is a flypaper effect on regional expenditures of Kuningan. It means that the Regional Government of Kuningan is still highly dependent on central government’s fund transfers. This research implies that (1) the Regional Government of Kuningan is expected to maximize the exploration of its local resources gradually, (2) it is necessary to optimize the supervision conducted by the Directorate General of Taxes (DGT) on taxpayers and to explore tax revenues from them and tax objects, (3) the local government needs to have adequate control systems to ensure compliance with management policy procedures, and (4) administrative procedure simplification is also necessary to provide convenience,  thereby increasing tax compliance and the percentage of local revenue.Keywords: GAF, LOSR, Expenditures, Flypaper Effect.